Absence of CD74 Isoform at 41kDa Prevents the Heterotypic Associations between CD74 and CD44 in Human Lung Adenocarcinoma-derived Cells. (17th November 2021) - Al Abdulmonem, Waleed; Rasheed, Zafar; Aljohani, Abdullah S. M.; Omran, Ola M.; Rasheed, Naila; Alkhamiss, Abdullah; A. M. Al Salloom, Abdulaziz; Alhumaydhi, Fahad; Alblihed, Mohamd A.; Al Ssadh, Hussain; Khan, Muhammad Ismail; Fernández, Nelson
ABSTRACT: Lung cancer is a leading cause of cancer-associated death in all over the globe. This study was undertaken to determine the expression and interaction of membrane-bound receptors CD74 and CD44 in human lung adenocarcinoma cells and their associated signaling was also attempted. Levels of CD74 and CD44 were studied in human lung adenocarcinoma-evolved cells A549 and H460. CD74-mediated downstream signaling was studied by the nuclear-transcription-factor NF-κB and prostaglandin E2 (PGE2 ) production. Flow-cytometric analysis showed that both CD74 and CD44 were perfectly expressed in A549 cells. Importantly, Western immunoblotting showed that A549 cells expressed only two isoforms of CD74 at 33 and 35 kDa but isoform at 41 kDa was absent. These results were verified in H460 cells. Confocal microscopy showed CD74 and CD44 was colocalized but heterotypic interaction between them was missing in both A549 and H460 cells. Activation of NF-κB and production of PGE2 in human lung cancer cells were comparable with other cancer cells. In conclusion, this is the first study that shows A549 and H460 cells expressed two distinctive isoforms of CD74 but isoform at 41 kDa was absent. Due to the absence of this isoform, the direct physical interaction between them CD74 and CD44 was lacking. Furthermore, the data also demonstrated that lacking of direct physical interaction between CD74 and CD44 had no effect on NF-κB activation and PGE2 production indicating that CD74-mediated downstream signaling occurs either through coreceptors or indirect interaction with CD44 in human lung cancer cells. Abbreviation : CD: cluster of differentiation; SCLC: small cell lung cancer; NSCLC: nonsmall cell lung cancer; SCC: squamous cell carcinoma; ADC: adenocarcinoma; LCC: large cell carcinoma